Regimes of the World (RoW): Opening New Avenues for the Comparative Study of Political Regimes - Lührmann, Anna; Tannenberg, Marcus; Lindberg, Staffan I. (2018)
Abstract: Classifying political regimes has never been more difficult. Most contemporary regimes hold de-jure multiparty elections with universal suffrage. In some countries, elections ensure that political rulers are - at least somewhat - accountable to the electorate whereas in others they are a mere window dressing exercise for authoritarian politics. Hence, regime types need to be distinguished based on the de-facto implementation of democratic institutions and processes. Using V-Dem data, we propose with Regimes of the World (RoW) such an operationalization of four important regime types - closed and electoral autocracies; electoral and liberal democracies - with vast coverage (almost all countries from 1900 to 2016). We also contribute a solution to a fundamental weakness of extant typologies: The unknown extent of misclassification due to uncertainty from measurement error. V-Dem's measures of uncertainty (Bayesian highest posterior densities) allow us to be the first to provide a reg